2018
DOI: 10.1177/1076029618776799
|View full text |Cite
|
Sign up to set email alerts
|

d-Dimer Assessment Improves the Simplified Pulmonary Embolism Severity Index for In-Hospital Risk Stratification in Acute Pulmonary Embolism

Abstract: d-dimer (DD) levels are used in the diagnostic workup of suspected acute pulmonary embolism (APE), but data on DD for early risk stratification in APE are limited. In this post hoc analysis of a prospective observational study of 270 consecutive patients, we aimed to optimize the discriminant capacity of the simplified pulmonary embolism severity index (sPESI), an APE risk assessment score currently used, by combining it with DD for in-hospital adverse event prediction. We found that DD levels were higher in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…There was a relationship between increased D-Dimer concentrations and clot burden, thrombus localization, major bleeding and RV dysfunction (18)(19)(20). Studies of D-Dimer in patients with PE have demonstrated various data regarding the severity of PE and early risk stratification (22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…There was a relationship between increased D-Dimer concentrations and clot burden, thrombus localization, major bleeding and RV dysfunction (18)(19)(20). Studies of D-Dimer in patients with PE have demonstrated various data regarding the severity of PE and early risk stratification (22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Kozlowska and colleagues studied 270 consecutive patients with acute PE. 41 In Cox's proportional hazard regression analysis, an hs-cTnT value > 14 ng/L was found to be associated with a nearly 10-fold higher risk (HR, 9.5; 95% CI, 1.8-70.4) of developing in-hospital adverse events (i.e., hemodynamic deterioration, need for rescue thrombolysis or cardiopulmonary resuscitation, mortality).…”
Section: Review Of Clinical Evidence Of the Role Of Hs-ctn In Pulmonamentioning
confidence: 98%
“…Hemodinamik olarak stabil olgularda düşük mortalite nedeniyle BNP veya NT-pro BNP yüksekliği olmayan hastaların erken taburcu olabileceği veya ayaktan tedavi edilebileceği ileri sürülmektedir (30) . (31) . Yüksek > 6 (prevalans %74) > 2…”
Section: Kardiyak Biyobelirteçlerunclassified